EXTRACURRICULAR MANAGEMENT AS A MARKETING STRATEGY FOR SUPERIOR SCHOOLS AT SDN BESUK AGUNG PROBOLINGGO - Fauzan, Ahmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This paper describes the management of extracurricular activities as a marketing strategy for excellent schools at the elementary school level, as it is understood that marketing is an exceptionally vital and quite significant activity that is directly felt and closely related to the surrounding community. Marketing strategy can be an essential indicator determining an educational institution's success in marketing activities, mainly in maintaining the value of schools that have achieved superior accreditation. The objectives of this study include; (1) describing extracurricular planning as a marketing strategy for a superior school at SDN Besuk Agung Probolinggo, East Java; (2) describing extracurricular implementation as a marketing strategy for excellent schools at SDN Besuk Agung Probolinggo, East Java; (3) describe extracurricular evaluation as a marketing strategy for excellent schools at SDN Besuk Agung Probolinggo, East Java. This research is a type of descriptive qualitative research. The data was collected using the methods of observation, interviews, and both print and electronic documentation. The research results show that; (1) The extracurricular planning process consists of five categories based on the interests of students, such as scouting; sport; dance art; gamelan music art; and religion; (2) The extracurricular process is scheduled between 14.00 and 16.00 WIB on Monday, Tuesday, Wednesday and Friday. At the same time, this is a strategy for promoting excellent schools (Accreditation A) socialized to parents and the wider community. Especially in the process of accepting new students every new school year at SDN Besuk Agung, as well as program activities at schools and related service programs; (3) The results of extracurricular evaluations that become additional specializations for students become material for study by school principals and policymakers who are under them to realize new extracurricular specializations in the next period.